Cost-effectiveness of nivolumab in squamous and non-squamous non-small cell lung cancer in Canada and Sweden: an update with 5-year data. (1st January 2021) - Chaudhary, Mohammad A.; Holmberg, Christoffer; Lakhdari, Khalid; Smare, Caitlin; Theriou, Chloi; Dale, Peter; Penrod, John R.
Abstract: Aims: Nivolumab has been approved for advanced squamous and non-squamous non-small cell lung cancer (NSCLC) following platinum-based chemotherapy in both Canada and Sweden. We aimed to determine the value-for-money of nivolumab versus docetaxel in a Canadian and Swedish setting based on 5-year data. Methods: These cost effectiveness analyses used partitioned survival models with three mutually exclusive health states: progression-free, progressed disease, and death. All clinical parameters were derived from two registration phase 3 randomized trials, CheckMate 017 and CheckMate 057, with a minimum follow-up of 5 years. Treatment duration was based on time-on-treatment data from the clinical trials. Costs were derived from published sources. The primary outcomes of the analyses were quality-adjusted life-years (QALYs), life-years gained, and incremental cost-effectiveness ratios (ICERs). The model input parameters for each analysis were chosen in line with guidance from the respective HTA authorities. Results: From a Canadian payer perspective, the ICERs were CAN140, 753 per QALY in the squamous population, and CAN173, 804 per QALY in the non-squamous population, assuming a 10-year time horizon and a 5% discount rate for both costs and outcomes. Sensitivity analyses demonstrated that changes to the discount rates for outcomes had the highest impact on the ICERs. In the Swedish analysis, the ICERs were SEK568, 895 per QALY in the squamous population and SEK662, 991 per QALY in the non-squamous population, assuming a 15-year time horizon, a 3% discount rate, and a 2-year maximum treatment duration for nivolumab. Sensitivity analyses demonstrated that the ICERs were most sensitive to changes in the discount rate for outcomes. Conclusion: These updated analyses, based on more mature trial data with a minimum follow-up of 5 years, generate more favorable ICERs versus the previously submitted HTA assessments that resulted in approval of nivolumab for patients with previously treated NSCLC in Canada and Sweden.